All in the family: The link between kin network bridging and cardiovascular risk among older adults. (October 2016) - Goldman, Alyssa W.
Abstract: While considerable work has examined the association between social relationships and health, most of this research focuses on the relevance of social network composition and the quality of dyadic ties. In this study, I consider how the social network structure of ties among older adults' close family members may affect cardiovascular health in later life. Using data from 938 older adults that participated in Waves 1 and 2 of the National Social Life, Health, and Aging Project (NSHAP), I test whether older adults who occupy bridging positions among otherwise disconnected or poorly connected kin in their personal social network are more likely to present elevated levels of C-reactive protein (CRP), a biomarker for cardiovascular risk. Results indicate that occupying a bridging position among family members is significantly associated with elevated CRP. This effect is unique to bridging kin network members. These findings suggest that ties among one's closest kin may generate important resources and norms that influence older adults' health, such that bridging kin network members may compromise physical wellbeing. I discuss these results in the context of prior work on social support, family solidarity, and health in later life. Highlights: Study examines social network bridging and cardiovascular disease (CVD) risk. Older adults that bridge kin are ∼65% more likely to present elevated CVD risk. This association is unique to bridging kin network members. Bridging kin may be linked to greater social strain and less social support. This association may be more consequential for women than for men.